Comparative Study of Product Quality Perception between Malaysian and Non-Malaysian Electrical Appliance among Tertiary Students - SHIAU WEI CHAN; M.F. Ahmad Ahmad; Fadillah Ismail; Yunos Ngadiman; Izzuddin Zaman; Siti Sarah Omar; Kian Yuen Tay (International Journal of Supply Chain Management, 2018)
The high quality of a product is much demanded by consumers today. However, it is difficult to understand the perceptions of consumers towards product quality. Thus, this study intends to identify the relationships between brand and nine product quality dimensions as well as to compare the difference in quality perception between Malaysian and Non-Malaysian electrical appliances amongst Universiti Tun Hussein Onn Malaysia students. This is a quantitative study. Nine research hypotheses were examined while considering the nine dimensions of product quality (performance, features, conformance, durability, reliability, serviceability, aesthetics, perceived quality, and environmentally friendly) which were believed to affect the consumers' perceptions of product quality. In this study, the respondents were students from the Faculty of Technology Management and Business, Universiti Tun Hussein Onn Malaysia. The data were analysed by using SPSS software. The result reveals that only two quality dimensions, i.e. feature and serviceability were significantly correlated with the brand. Besides that, four quality dimensions, i.e. performance, features, aesthetics, and perceived quality had a significant difference in quality perceptions between Malaysian and Non-Malaysian electrical appliances. The result of this study will help to provide guidance and information for future research in the field of electronics.